Evaluating nursing hours per patient day as a nurse staffing measure. (17th November 2015) - Min, Ari; Scott, Linda D.
Abstract : Aims: To identify the techniques used to measure nurse staffing and to evaluate the reliability, validity and limitations of nursing hours per patient day (NHPPD). Background: Numerous studies have attempted to identify appropriate nurse staffing levels; however, variations in nurse staffing measures may have caused inconsistent findings regarding the relationships between nurse staffing and quality of care. Evaluation: Seventeen studies using nurse staffing measures were reviewed. Key issues: Six common nurse staffing measures were identified: nurse‐to‐patient ratios, full‐time equivalents, NHPPD, skill mix, nurse‐perceived staffing adequacy and nurse‐reported number of assigned patients. Conclusions: Among nurse staffing measures, NHPPD is the most frequently used and is considered to be highly beneficial. This measure shows some evidence of high inter‐rater reliability. The predictive validity of NHPPD for patient falls is high, whereas that for pressure ulcers is low. Implications for nursing management: For NHPPD to be applied more effectively as a nurse staffing measure, there is a need for additional reliability testing in various types of units with large sample sizes; further validity research for additional patient outcomes; appropriate adjustments in its application to capture variations in the characteristics of nurses, patients and hospital units; and a consistent data collection procedure.